Modelling, Computation and Optimization in Information Systems and Management Sciences : Proceedings of the 4th International Conference on Modelling, Computation and Optimization in Information Systems and Management Sciences - MCO 2021 - Le Thi, Hoai An; Pham Dinh, Tao; Le, Hoai Minh (Lecture Notes in Networks and Systems, 2022)
The proceedings consist of 34 papers which have been submitted to the 4th international conference on Modelling, Computation & Optimization in Information Systems and Management Science (MCO 2021) held on 11-13 December, 2021 at Hanoi, Vietnam. The book is composed of 3 parts: Optimization of complex systems - models and methods, Machine Learning - algorithms and applications, and Cryptography. All chapters in the books discuss theoretical and algorithmic as well as practical issues connected with modelling, computation & optimization in Information Systems and Management Science. Researchers and practitioners in related areas will find a wealth of inspiring ideas and useful tools & techniques for their own work.